2023
DOI: 10.34067/kid.0006832022
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination and New Onset Glomerular Disease: Results from the IRocGN2 International Registry

Abstract: Background:Cases of de novo glomerular disease with various renal histologies have been reported after vaccination against SARS-CoV-2. Causality has not been established and the long-term outcomes are not known. To better characterize the glomerular diseases and clinical course/outcomes, we created the International Registry of COVID-19 vaccination and Glomerulonephritis (IRocGN2) to study in aggregate de novo glomerulonephritis cases suspected after COVID-19 vaccine exposure Methods:A RedCap survey was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Minimal change disease and IgA nephropathy were the most common among these, and the others included pauci-immune CrGN, membranous nephropathy, and collapsing GN. 6 7 8 9 10 11 12 13 14 To our knowledge, this is the first case report of de novo “ANCA-negative” pauci-immune CrGN with extrarenal involvement after COVID-19 mRNA vaccination in an adult patient, with prominent extrarenal involvement which is unusual in ANCA-negative vasculitis. 15 …”
Section: Discussionmentioning
confidence: 81%
“…Minimal change disease and IgA nephropathy were the most common among these, and the others included pauci-immune CrGN, membranous nephropathy, and collapsing GN. 6 7 8 9 10 11 12 13 14 To our knowledge, this is the first case report of de novo “ANCA-negative” pauci-immune CrGN with extrarenal involvement after COVID-19 mRNA vaccination in an adult patient, with prominent extrarenal involvement which is unusual in ANCA-negative vasculitis. 15 …”
Section: Discussionmentioning
confidence: 81%
“…We observed that almost all IgAN exhibited gross hematuria (within 2–3 days) after COVID-19 vaccination, similar to the rapid development of IgAN following upper respiratory tract or gastrointestinal tract infection. The post-vaccination glomerular disease mostly evaluated by the changes in eGFR and proteinuria other than hematuria in cohort studies may make IgAN largely underestimated ( 16 , 28 ). As the second most nephritic form in this renal registry, all four patients with de novo biopsy-proven AAN also exhibited nephrotic-range proteinuria to indicate podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy and minimal change disease were the most dominant kidney disease (more common after mRNA-based vaccines). Standard immunosuppression regimens led to disease remission [72 ▪ ]. Another study investigated the risks of relapsing glomerular disease using data from a centralized pathology registry.…”
Section: Sars-cov-2 Vaccine Associated Glomerular Diseasementioning
confidence: 99%